2020
DOI: 10.2139/ssrn.3558273
|View full text |Cite
|
Sign up to set email alerts
|

Cold Creep of Titanium: Analysis of Stress Relaxation Using Synchrotron Diffraction and Crystal Plasticity Simulations

Abstract: It is well known that titanium and some titanium alloys creep at ambient temperature, resulting in a significant fatigue life reduction when a stress dwell is included in the fatigue cycle. It is thought that localised time dependent plasticity in 'soft' grains oriented for easy plastic slip leads to load shedding and an increase in stress within a neighbouring 'hard' grain * Corresponding author E-mail address: yi.xiong@materials.ox.ac.uk (Yi Xiong) have a significant effect on stress redistribution to hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…With increasing stress levels, but still below σ0.2%, both microstructure conditions have shown that prismatic <a> slip starts to become the dominant slip mode. This is in good agreement with previous studies where deformation studies well beyond the proof stress have always shown dominance of prismatic <a> slip [29,91]. It is noticeable that the sample with the finer transformation product exhibits a higher frequency of pyramidal slip at all load steps, with most of it being localised in the transformed β phase.…”
Section: Slip Activation Mechanisms Below the 02% Proof Stresssupporting
confidence: 92%
See 1 more Smart Citation
“…With increasing stress levels, but still below σ0.2%, both microstructure conditions have shown that prismatic <a> slip starts to become the dominant slip mode. This is in good agreement with previous studies where deformation studies well beyond the proof stress have always shown dominance of prismatic <a> slip [29,91]. It is noticeable that the sample with the finer transformation product exhibits a higher frequency of pyramidal slip at all load steps, with most of it being localised in the transformed β phase.…”
Section: Slip Activation Mechanisms Below the 02% Proof Stresssupporting
confidence: 92%
“…However, the reported critical resolved shear stress (CRSS) values for basal <a> and prismatic <a> slip in Ti-alloys cover a wide range and in some studies basal <a> slip is said to be more difficult, i.e. CRSS(Ba)>CRSS(Pr) [20,[23][24][25][26][27][28][29] and in others easier i.e. CRSS(Ba)<CRSS(Pr) [18,19,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron diffraction offers the advantage of being able to examine grain-scale response through measurement of lattice strains in-situ while probing a statistically significant number of grains. In the last decade, synchrotron diffraction has been used more widely to characterise the behaviour of titanium alloys, including of forged Ti64 under tensile loading [22], mill-annealed Ti64 [23], CP Ti [24,25], Ti-7Al [26] and equiaxed Ti64 [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…While some of the previous work pays attention to stress relaxation effects during extended hold periods in CP Ti [25], there are no studies that examine the lattice strain response of dwell fatigue over a sustained number of cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, significant advances have been made in techniques used to determine material properties on an ever finer length scale, allowing for a better understanding of basic material property-microstructure relationships [1][2][3]. These developments have provided crucial insight into fundamental materials science, facilitating more accurate multiscale modelling [4][5][6][7][8][9][10], as well as the necessary property assessment for modern manufacturing processes with small features [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%